(untitled) (Educação e Pesquisa, 2021)
The article focuses on the professional development processes of higher education professors, looking especially at the teaching dimension. It aims to capture different profiles of pedagogical orientation in a group of teachers from three higher education institutions located in Portugal, in the Lisbon and Tagus Valley area. Also, it seeks to understand which factors (endogenous and exogenous) contribute to a greater distance or a greater proximity to a learning-oriented pedagogical profile. Interviews and bibliographic review have been the starting point to build a questionnaire with three scales, namely, levels of involvement and personal commitment to the profession, teaching concerns, and factors of change. The results reveal the presence of distinct pedagogical orientation profiles, with one group showing a more primary stage of professional development, basically centered on themselves and on their scientific proficiency; the other group, with a higher degree of development, and hegemonically oriented towards students and their learning; and a third group, without a dominant focus, which apparently brings together teachers influenced by their careers requirements, particularly regarding research and scientific production.